Estabilização do carbono de resíduos culturais no solo com o uso de xisto retortado - Leão, Ricardo Elso (2014)
The impact of retorted oil shale (ROS) addition on the dynamics of carbon (C) of crop residues (CR) in the soil is little known. Under laboratory conditions, the present study aimed to evaluate the residual and immediate effects of ROS on C mineralization of CR, water stability aggregates and storage C in the particulate (>53 μm) and associated minerals fractions (<53μm) of organic matter (OM) of a Hapludalf. In experiment 1, treatments consisted of soil samples from plots that received four additions of ROS, totaling 0, 6,000 and 12,000 kg ha-1. In experiment 2, treatments consisted of soil with no history of application of ROS (0 kg ha-1), that in the laboratory received three doses of ROS (0, 1,500 and 3,000 kg ha-1). In both experiments, the treatments were evaluated in the presence (3,000 kg ha-1) and absence of leaves and stalks of soybeans. The release of C-CO2 was evaluated for 80 days and at the end of the experiment determined the aggregate stability and C storage in different OM fractions. The addition of CR in soil with a history of ROS addition did not alter the release of C-CO2 and also did not reduce the apparent mineralization of C of RC compared to addition of these residues in soil with no history. In experiment 2, there was a reduction in the release of C-CO2 compared to the control only the treatment with stalks + 3000 kg ROS ha-1. In experiment 2, the treatment stalks + 3000 kg ROS ha-1 provided an increase in aggregate stability compared with treatment with only stalks. In experiment 1, the ROS addition tended to higher retention of C stalks and leaves in the soil. In experiment 2, the application of CR + ROS promoted greater retention of soil C only in the treatment with leaves. Under laboratory conditions, the soil with a history of ROS addition did not affect mineralization and retention of crop residue C added to soil. Besides, the ROS showed an immediate effect, reducing C mineralization from stalks and increasing retention of C from leaves added to the soil.